Converting tests of fundamental social, cognitive, and affective processes into clinically useful bio‐behavioral markers for neurodevelopmental conditions. Issue 5 (3rd April 2019) - Loth, Eva; Evans, David W.
Abstract : Biomarker discovery has become a central topic in neurodevelopmental research. A validated biomarker could be any objective measure or test that has clinical utility for diagnostic, stratification, or predictive purposes, or that can be used to objectively measure therapeutic efficacy. Here we discuss the potential and challenges of converting tests of fundamental social, cognitive, emotional and motivational processes into clinically useful bio‐behavioral markers for neurodevelopmental conditions. Given the broad clinical and etiological heterogeneity of many neurodevelopmental conditions, we propose moving the focus from identifying group‐defining characteristics to creating cross‐domain bio‐behavioral profiles at the individual level. We outline steps to develop tests that reflect the relevant domains and that are comparable, engaging and sensitive across large age and ability ranges. Analytical validation of these tests requires creating age norms, and optimizing psychometric properties. Individual bio‐behavioral fingerprints of strengths and difficulties across domains can then be combined with multivariate approaches to identify "subgroups." This may help researchers and clinicians to compare individuals with and without intellectual disability, track developmental stability versus changes, and facilitate family genetic studies. Clinical validation requires including these tests in multidisciplinary, longitudinal and/ or intervention studies to ascertain whether particular subgroups differ in terms of their etiology, clinical symptom profile, prognosis or therapeutic benefit. Potential advantages of bio‐behavioral tests over other biomarker methodologies, such as neuroimaging measures, include the low cost, ease of administration and analysis, low risk, and scalability through on‐line assessments or tablet applications. This article is categorized under: Neuroscience > Development Psychology > Theory and Methods Neuroscience > Clinical Neuroscience Neuroscience > Cognition Abstract : Outline of steps required for converting experimental psychological tests of social, cognitive, emotional and motivational processes into bio‐behavioral markers for neurodevelopmental disorders. (a) Development of tablet battery. (b) Establishing cross‐domain cognitive profiles for each individual. (c) Identifying subgroups. (d) Validation and qualification of biomarkers, and use in clinical trials.